Flux measurements of short-time sediment traps from Young Sound, NE Greenland - Ingrid Wiedmann; Maria Lund Paulsen; Johnna M Holding; Mie Hylstofte Sichlau Winding; Hans Roy; Mikael K Sejr; Katja Laufer-Meiser (PANGAEA, 2025)
This dataset contains measurements of fluxes of POC and PON (incl. C/N and δ13C and δ15N in the water column of Young Sound. Short-term sediment traps were deployed in August 2019.
In: Wiedmann, I et al. (2025): Impact of Different Types of Meltwater Runoff on Pelagic and Benthic Processes in Young Sound, NE Greenland [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.986456